STUDI TENTANG PENGARUH KEPEMIMPINAN KEPALA MADRASAH, KINERJA MENGAJAR GURU, DAN BUDAYA MADRASAH TERHADAP KEPUASAN SISWA DAN DAMPAKNYA PADA PRESTASI BELAJAR DI MADRASAH ALIYAH KOTA DAN KABUPATEN TASIKMALAYA - Saripudin, _ (2015)
The development of madrasah aliyah students' learning achievements currently seems to be in the low category. The phenomenon is expected to influence on the community's trust with the service of catering to students' learning needs. Based on theoretical studies, the issue is affected by madrasah principal's leadership, teacher's teaching performance, and madrasah culture. The improvement in the catering of learning needs aims to meet students' satisfaction in madrasah aliyah that will impact on their learning achievements. This research employed quantitative approach through survey. Research data on Madrasah Principal's Leadership used teachers as respondents, and data on Teacher's Teaching Performance and Madrasah Culture used students as the respondents. Research sample was determined using proportionate stratified random sampling. Data were collected through questionnaires employing descriptive data processing, and hypothesis test was done with SPSS program. Research findings show that Madrasah Aliyah Principal's Leadership in making changes to create innovations, solve problems and provide solutions to problems was still in the low category. Madrasah Principal's Leadership as an example and important figure as well as motivator for good class atmosphere was in the moderate category. Madrasah Aliyah Teacher's Teaching Performance in making teaching and learning interesting and fun as well as making assessment (affective and psychomotor domains) and assignment was in the low category, while in tutoring it was in the moderate category. Madrasah Culture in the forms of values and behaviors was in the moderate category, while the implementation of norms was in the low category. Students' satisfaction of learning facilities was in the very low category, teaching and learning service moderate category, guidance service high category, and regulation implementation in the improvement of teaching and learning low category. Students' learning achievements in academic field was in the moderate category. The achievements of state madrasah aliyah students were higher than those of the private madrasah, and students in both high level state and private madrasah had better learning achievements. Based on the hypothesis test, Madrasah Principal's Leadership, Teacher's Teaching Performance, Madrasah Culture simultaneously had influence on students' satisfaction. This showed that the improvement of one variable, namely Madrasah Principal's Leadership or Teacher's Teaching Performance, or Madrasah Culture will influence the improvement in students' satisfaction. Students' satisfaction had influence on learning achievements, showing that the levels of students' achievement are affected by their satisfaction. The research has recommended one of the alternatives to improve students' satisfaction and its impact on learning achievements.